Effectiveness of Cognitive Behavioral Group Intervention on Acculturation: A Study of Students in Hong Kong from Mainland China. (January 2017) - Pan, Jia-Yan; Ng, Petrus; Young, Daniel Kim-Wan; Caroline, Schoepf
Objective: This study examined the effectiveness of group cognitive behavioral intervention (CBI) in improving mental health and promoting postmigration growth for Mainland university students in Hong Kong. Methods: Thirty-six Mainland students with mild-to-moderate levels of psychological distress have completed a 8-session CBI group. Various mental health measures have been administered at the pre-, post-, and 3-month follow-up tests. Results: The levels of psychological distress, acculturative stress, and negative emotions and negative thoughts of the participants were significantly reduced, while their positive emotions and postmigration growth were significantly increased upon completion of the CBI group. The positive effects were maintained at 3-month follow-up. Conclusions: CBI group appears to be an effective intervention approach for improving the mental health and promoting postmigration growth for Mainland university students in Hong Kong. Implications for social work practices when engaging with Chinese international students were provided.